Research on the Correlation Between Emotional-Gnostic and Personal Characteristics with Parameters of Adolescents’ Creativity - Chebykin , Оleksii; Sytnik , Svitlana; Massanov , Anatolii; Pavlova , Iryna (Insight: the psychological dimensions of society, 2024)
The aim is to research the correlation of the most significant emotional-gnostic and personal characteristics with parameters of adolescents’ creativity. Methods. 150 adolescents aged 10–12 took part in the research. They gave answers to the statements of the method, aimed at determining the manifestation of creativity features, namely: an adapted author’s expert assessment, based on the diagnostic technique of creative personality traits by O. Tunik (2013) and the questionnaire of personal propensity for creativity by G. Davis (1989); as well as for the study of emotional-gnostic and personal characteristics: the children’s version of the multifactorial personality questionnaire by R. Cattell et al. (1993); scale of personal anxiety by H. Prykhozhan (2007). The results. A certain variability in the manifestation of creativity features of the subjects and the absence of a high propensity for creativity was found out on the general sample of subjects. Direct correlations of indicators of the manifestation of creativity traits with impatience (р < .010), independence (р < .010), emotional stability (р < .010), determination (р < .010), psycho-emotional stress (р < .010), extraversion (p < .050), self-confidence (p < .050) were established. Using cluster analysis, groups of adolescents with significant differences in manifestations of creativity traits and propensity to this activity were identified. In particular, these are 1) children who were inclined to creativity and were able to realize it at the highest level among other adolescents; 2) children who were able to show creativity and had no interest in it; 3) subjects who were inclined to engage in creativity, however, their manifestations of creativity were insignificant. Analysis of variance of emotional- gnostic personality indicators was applied, and it was established that the groups differ in manifestations of psycho-emotional stress (р < .01), extraversion (р < .05) and conscientiousness (р < .01). Discussion and conclusions. It was clarified and explained that the set of emotional-gnostic and personal characteristics, which have statistically significant correlations with the manifestations of creativity features, include the following: a high level of psycho-emotional stress, activity in social interactions, openness, impermanence, flexibility and uncertainty in decision-making.
Keywords: traits of a creative personality, propensity for creativity, psycho-emotional stress, extraversion, conscientiousness, anxiety.